Uji Kadar Hambat Minimum (KHM) dan Kadar Bunuh Minimum (KBM) ekstrak daun kirinyuh (Chromolaena odorata) dari geothermal Ie Seum Aceh Besar terhadap Staphylococcus aureus - Munira Munira; Muhammad Nasir (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: Chromolaena odorata plant is a weed that grows abundantly in various places, including geothermal areas. Its leaves contain chemical compounds such as alkaloids, flavonoids, steroids, and tannins that can function as antibacterials.Objectives: The study aims to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of ethanol extract of Chromolaena odorata leaves grown in the geothermal area of Ie Seum Aceh Besar against Staphylococcus aureus.Methods: The study was conducted at the Fundamental Microbiology Laboratory of Aceh Besar in June 2022. The MIC and MBC tests of ethanol extract of Chromolaena odorata leaves from the geothermal area of Ie Seum Aceh Besar were performed using the liquid dilution method. The concentrations of the extract used were 1%, 3%, 5%, 7%, and 10%. The MIC was determined based on the turbidity or clarity of the test solution, while the MBC was determined by streaking each concentration of the extract/test solution on agar media. Data analysis was performed descriptively in terms of the lowest concentration of the extract that could inhibit and kill Staphylococcus aureus.Results: The results showed that the ethanol extract of Chromolaena odorata leaves from the geothermal area of Ie Seum Aceh Besar had a MIC value of 5% and an MBC value of 7% in inhibiting the growth of Staphylococcus aureus.Conclusion: Based on the study, it can be concluded that the ethanol extract of Chromolaena odorata leaves from the geothermal area of Ie Seum Aceh Besar is able to inhibit the growth of Staphylococcus aureus from a concentration of 5% and able to kill Staphylococcus aureus from a concentration of 7%.